Development of a Decision Aid about fertility preservation for women with breast cancer in the Netherlands. (December 2013) - Garvelink, Mirjam M.; ter Kuile, Moniek M.; Fischer, Maarten J.; Louwé, Leoni A.; Hilders, Carina G. J. M.; Kroep, Judith R.; Stiggelbout, Anne M.
Abstract: Objectives : To improve information provision about fertility preservation for breast cancer patients in the Netherlands, a web-based Decision Aid (DA) with additional values clarification exercise was developed according to the International Patient Decision Aid Standards criteria. This study reports on development of the DA. Methods : Development consisted of four stages: (I) development of a draft DA, (II) acceptability of the draft DA to patients, (III) understanding (knowledge) in healthy populations, (IV) acceptability of the revised DA among patients and physicians. The study population consisted of 185 participants: 20 patients, 17 physicians and 148 healthy volunteers. Results : The draft DA was considered to be relevant and understandable by patients, physicians and healthy volunteers. The values clarification exercise needed adaptation in explanation and navigation, which was done after stage II. Knowledge scores improved by 18% for lower educated women (from 4.1 (41%) to 5.9 (59%) correct answers), and by 34% for higher educated women after viewing the website (from 3.9 (39%) to 7.3 (73%) correct answers). Design of the DA was evaluated to be clear, but not always very appealing. Conclusions : The DA was regarded as a relevant source of information that seemed coherent and understandable.